The Effectiveness of Silver Nanoparticles Synthesized from Rosella (Hibiscus sabdariffa L.) Flower Extract for Photodynamic Antimicrobial Therapy Against Staphylococcus - Ahmad Faisal Islamudin; Fransiska Maria Aprihapsari; Elmira Rofida Alhaq; Rohadatul Aisya; Khusnul Ain; Suryani Dyah Astuti; Inten Firdhausi Wardhani; Amun Amri (Institute of Topical Disease Universitas Airlangga, 2026)
Green synthesis of silver nanoparticles (AgNPs) using plant extracts has drawn growing interest for its potential to enhance antibacterial activity. This study evaluates the antibacterial performance of AgNPs synthesized from rosella (Hibiscus sabdariffa L.) flower extract, assessed through several characterization and antibacterial tests. The extract was prepared by macerating 10 g of rosella powder in 150 mL double-distilled water for five days, then filtering the mixture. It was combined with 3 mM AgNO₃ at a 1:9 ratio and exposed to microwave irradiation at 200 W for 5, 10, 15, and 20 minutes to examine how irradiation time affects nanoparticle formation. UV-Vis spectroscopy and particle size analysis (PSA) were used for characterization, while antibacterial activity was tested via disc diffusion and photodynamic therapy (PDT) with a red laser. UV-Vis spectra showed absorption peaks between 506 and 519 nm, confirming AgNP formation, and PSA showed that longer microwave exposure produced smaller particles, ranging from 1 to 27 nm with an average of 5.74 nm. The disc diffusion assay yielded only a 1.85 mm inhibition zone, indicating weak antibacterial activity against S. aureus. PDT, however, achieved markedly better results, with up to 68% bacterial reduction under optimal conditions, though the AgNPs-R4 sample showed reduced efficiency due to a mismatch between laser wavelength and particle absorbance—smaller particles have a wider energy gap, shifting absorbance to shorter wavelengths. These results highlight the need to optimize synthesis conditions for consistent, maximal antibacterial performance.